ANDISOLS DERIVED FROM ACID PYROCLASTIC LIPARITE TUFF : THEIR PROPERTIES AND THEIR MANAGEMENT STRATEGY FOR AGRICULTURAL DEVELOPMENT - YATNO, EDI; SUHARTA, NATA (Jurnal Tanah dan Iklim (Indonesian Soil and Climate Journal), 2011)
The characterizations of Andisols from acid pyroclastic liparite tuff have been studied. Six soil profiles were made in the field, and 29 soil samples were taken for chemical, mineralogical and physical analyses in laboratory. Results indicate that sand mineral composition of Andisols was dominated by biotite, quartz, and sanidine, while the clay mineral was dominated by allophane. Soil bulk density is low (0.47-1.00 g cm-3), while total porosity is high (53-80%). Soil reaction is slightly acid (pH 5.5-6.0) to very acid (pH< 4.5), poor of nutrients, have a high to very high of P retention (>80%), high (>3%) to very high organic carbon (>5%) and high potential K (>41 mg 100g-1). The high value of organic carbon positively has relationship with N and soil cation exchange capacity, while the P retentionpositively has relationship with amorphous material in the form of Alo+0.5 Feo. Andisols investigated were classified as Medial, amorphic, isothermic, Acrudoxic Hapludands (UG 444 and MD 121 ), Medial, amorphic, shallow, isothermic, Duric Hapludands (KR 227), and Medial, amorphic, shallow, isothermic, Acrudoxic Hapludands (KR 190, AI 1045 and KR 1188). The characterization of Andisols is very useful in the soil management planning on Andisols land. Planting some vegetation that tolerant with soil acidity and soil conservation to protect organic matter from erosion hazard should be become priority. Maintain land cover of Andisols is a good way to protect Andisols from erosion process.